Surrogate Model-based Optimization of a Biplane Unmanned Aerial Vehicle Wing Using Genetic Algorithm and Response Surface Methodology - Eraslan, Yüksel (IIUM Engineering Journal, 2026)
Multi-wing aerial vehicle designs have existed since the early days of aviation; however, they are not commonly employed in modern designs, as advances in materials technology have enabled the structurally feasible high-aspect-ratio monoplane configurations. Nevertheless, the application has the potential to serve as a solution in the field of mini unmanned aerial vehicle (UAV) design, offering the advantage of a smaller wing span. The most popular multi-wing application, the biplane, features two wings mounted in parallel and is typically characterized by the geometric terms decalage, stagger, and gap, which should be optimized during the design process. This study focuses on aerodynamic optimization of a biplane wing to maximize the lift-to-drag ratio (CL/CD) and the CL3/2/CD by optimizing the aforementioned geometric parameters. To this end, the aerodynamic analysis method was initially validated by comparing it with wind-tunnel data for a monoplane wing reported in the literature. The Response Surface Method (RSM) was used to assess the effects of the design parameters and to generate surrogate models for CL/CD and CL3/2/CD. The optimal design was determined using the genetic algorithm. The results indicated that decalage and gap distance primarily determine range improvement, whereas gap and stagger are the primary parameters for improving endurance. The applied optimization approach resulted in improvements of 10.93% in range and 46.63% in endurance relative to the base biplane configuration. ABSTRAK: Reka bentuk kenderaan udara berbilang sayap telah wujud sejak awal perkembangan penerbangan; namun, ia jarang digunakan dalam reka bentuk moden berikutan kemajuan teknologi bahan yang membolehkan nisbah-aspek-tinggi konfigurasi monosayap lebih berdaya struktur. Namun, aplikasi berbilang sayap berpotensi menjadi penyelesaian reka bentuk kenderaan udara tanpa pemandu bersaiz kecil (mini UAV), khususnya dengan kelebihan bentangan sayap lebih kecil. Konfigurasi berbilang sayap iaitu paling lazim, sayap berkembar (biplane), merujuk kepada dua sayap yang disusun selari dan dicirikan oleh parameter geometri utama seperti sela, aturan, dan jurang, perlu ditentukan secara optimum dalam proses reka bentuk. Kajian ini memfokuskan kepada pengoptimuman aerodinamik sayap berkembar bagi memaksimumkan nisbah angkat kepada seretan (CL/CD) dan CL3/2/CD melalui pemilihan optimum parameter geometri tersebut. Kaedah analisis aerodinamik terlebih dahulu disahkan melalui perbandingan data terowong angin bagi monosayap yang dilaporkan dalam literatur. Kaedah Permukaan Tindak Balas (Response Surface Method, RSM) digunakan bagi menilai kesan parameter reka bentuk dan model pengganti bagi CL/CD dan CL3/2/CD, manakala reka bentuk optimum ditentukan menggunakan algoritma genetik. Keputusan menunjukkan bahawa sela dan jurang merupakan parameter utama dalam peningkatan jarak terbang, manakala jurang dan aturan lebih dominan dalam meningkatkan daya tahan penerbangan. Pendekatan pengoptimuman yang dicadangkan menghasilkan peningkatan sebanyak 10.93% dari segi jarak dan 46.63% dari segi daya tahan berbanding konfigurasi sayap berkembar asas.